Vehicle-to-grid: Impacts on the electricity market and consumer cost of electric vehicles - Mads Greaker; Cathrine Hagem; Stef Proost (Statistics Norway, Research Department, 2019)
Higher battery storage capacity in electric vehicles (EV) can potentially serve two purposes: First, the larger the capacity, the less need for inconvenient recharging during long trips. Second, the larger the capacity, the larger the potential gains from vehicle-to-grid (V2G) electricity supply during peak prices or during periods of imbalance. We present an analytical model for the intertwinement of the consumers' choice of battery capacity and the potential for supplying power to the electricity market. We show that V2G increases the consumers' choice of battery capacity, and it may reduce the cost of owning an EV vis-à-vis a traditional car. Furthermore, V2G alleviates the capacity pressure on peak hours, and thereby reduces the need for investment in backup power, saving social costs. Based on a future scenario for the Belgian electricity market, we provide a numerical illustration indicating that the savings may be substantial.
Keywords: Q41; Q42; Q54; R42; 330; Electric vehicles; Vehicle-to-grid; V2G; Electricity market